Education for Pregnant Women and Cadres as an Effort to Optimize the Achievement of Exclusive Breastfeeding in Stunting Prevention - Kristiyanti, Rini; Khanifah, Milatun; Subowo, Edy; Kusuma, Nur Intan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Exclusive breastfeeding for the first six months of a baby's life is the gold standard in infant and child feeding recommended by WHO and UNICEF. Breast milk contains the complete nutrition that babies need. Only breastfeeding for infants aged 0-6 months is sufficient for all the nutritional needs of infants. This program aimed to increase mothers' understanding of the importance of exclusive breastfeeding, increase mothers' self-efficacy for breastfeeding, and mothers' readiness to face the breastfeeding process. The program is carried out by providing education, demonstrations, and breastfeeding assistance, as well as evaluation monitoring. The activity was attended by nine third-trimester pregnant women and 11 cadres, all of whom were unemployed. Providing education and training about the importance of breastfeeding for reducing can increase knowledge about exclusive breastfeeding. Breastfeeding self-efficacy was also measured and obtained an average score of 34 out of a total score of 56. The variation in breastfeeding self-efficacy was 4,153, with a minimum score of 34 and a maximum of 39. The results of breastfeeding assistance and evaluation showed that mothers can breastfeed well and only give breast milk to the baby. This program is expected to contribute to increasing breastfeeding coverage to reduce stunting in children.